Assessment of the relationship between body mass index (BMI) and blood pressure among children aged 9–15 years - Łoboda, Dorota (Journal of Education, Health and Sport, 2025)
Introduction: The increasing prevalence of overweight and obesity among children is a significant public health issue. These conditions are strongly associated with elevated blood pressure, which may lead to primary hypertension already in childhood. Objective: The objective of this study was to assess the relationship between excessive body weight and the risk of hypertension in children aged 9–15 years. Material and methods: The study involved a diagnostic survey and blood pressure measurements in a group of children hospitalized in pediatric and nephrology wards. Questionnaire SF-FFQ4PolishChildren questionnaire was used to assess nutritional knowledge and lifestyle. Results: The findings show a significant correlation between BMI values and elevated systolic and diastolic blood pressure in the study group. Children with overweight or obesity were more likely to exhibit hypertension or prehypertension. Additionally, the general level of knowledge regarding healthy eating and physical activity was low. Conclusions: Overweight and obesity significantly increase the risk of hypertension in children. Early prevention, including education on healthy lifestyles and nutritional habits, is essential.